Integration of hydrogels in microfabrication processes for bioelectronic medicine: Progress and outlook - Saghir, Saloua; Imenes, Kristin; Schiavone, Giuseppe (Frontiers in Bioengineering and Biotechnology, 2023)
Recent research aiming at the development of electroceuticals for the treatment of medical conditions such as degenerative diseases, cardiac arrhythmia and chronic pain, has given rise to microfabricated implanted bioelectronic devices capable of interacting with host biological tissues in synergistic modalities. Owing to their multimodal affinity to biological tissues, hydrogels have emerged as promising interface materials for bioelectronic devices. Here, we review the state-of-the-art and forefront in the techniques used by research groups for the integration of hydrogels into the microfabrication processes of bioelectronic devices, and present the manufacturability challenges to unlock their further clinical deployment.